Bangladesh and the Banality of Violence: Civility, Culture, and Crime - Khondker, Habibul Haque (Crime, Criminal Justice, and the Evolving Science of Criminology in South Asia, 2017)
The United Nations Office on Drugs and Crime’s 2011 study on global violence estimated that if measured by data from public health sources alone, Bangladesh has the highest rate of violence (8.5 homicide per 100,000 population, higher than the global average) within the region of South Asia. The World Health Organization’s World Report on Violence and Health defines violence as the intentional use of physical force or power, threatened or actual, against oneself, another person, or against a group or community, that either results in or has a high likelihood of resulting in injury, death, psychological harm, or deprivation. From this larger perspective, the rate and the incidence of violence in Bangladesh, taking into account the incidence of different forms of violence such as corporal violence, interpersonal violence, intimate partner violence, sexual violence, political violence, religious violence, and community violence, would be much higher than what is estimated by United Nations Office on Drugs and Crime’s 2011 study on global violence. This chapter examines this problematic of violence in Bangladesh. The core thesis is that the banality of violence in Bangladesh is related to the lack of a culture of civility—a broad cultural code and a social compact where tolerance, responsibility, and respect are the core values. Following Norbert Elias, one can argue that these values evolve with the evolution of civilization. With the evolution of modern civilization, particularly in the West, violence, in general, has declined because of the exclusive and legal monopoly of power in the hands of the state. Bangladesh must strengthen the state, however, not just by modernizing law and law enforcement but also by creating a culture of democracy, the rule of law, human rights, and equal justice. These values, in turn, will strengthen the culture of civility, and a strong culture of civility may lead to the decline of violence.